Improve resiliency through operational risk management: Case study in coffee shop ABC - Ongkosongo, Anindya Divanata; Wijayati, Nureni (International Journal of Financial, Accounting, and Management, 2024)
Purpose: The purpose of this research is to enhance the competitiveness of SMEs by creating operational risk management using ISO 31000:2018. This includes the process of identifying, evaluating, and mitigating risks in operational processes and will be applied to ABC Coffee Shop. This research is important considering that SMEs are one of the driving forces of the country's economy, but have a high failure rate due to intense competition and a tendency to be weak in various areas. Method: The research utilized a qualitative descriptive case study method, involving primary data gathered through interviews with internal MSME stakeholders, as well as secondary data. This study aims to provide valuable insights for MSMEs, offering competitive solutions to help them thrive and remain competitive. Results: The research results indicate that MSME Coffee Shop ABC faces 12 operational risks, with two posing an extreme level of risk that requires immediate attention. Limitations: We recognize that risk management applies only to the MSME ABC Coffee Shop and focuses on operational risks. However, further research should address the overall risk to provide a broader picture of these findings.   Contribution: ABC-MSMEs should consider these findings when making decisions regarding future risk management. Additionally, MSMEs must consider these factors when planning business strategies and making decisions to achieve higher financial performance. Novelty: To the best of our knowledge, this is the first study to implement risk management in MSME coffee shops using ISO 31000:2018.